2020
DOI: 10.1177/1060028020925558
|View full text |Cite|
|
Sign up to set email alerts
|

Emergency Authorization of Chloroquine and Hydroxychloroquine for Treatment of COVID-19

Abstract: The world is suffering a respiratory pandemic disease caused by a novel coronavirus (2019-nCoV), commonly known as COVID-19 (coronavirus disease 2019). The Food and Drug Administration issued an emergency authorization for chloroquine and hydroxychloroquine as experimental treatments for COVID-19 leading to a shortage of both medications. A literature review conducted in April 2020 shows a lack of high-quality data available, resulting in ambiguous guideline recommendations. Decisions to use either dr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 13 publications
(34 reference statements)
0
12
0
Order By: Relevance
“…Several drugs have recently been either suggested or being clinically administered to relive the symptoms of covid-19. These include dapagliflozin (sodium glucose cotransporter 2; SGLT2 inhibitor; an antidiabetic), Lopinavir/ Ritonavir, Darunavir/Umifenovir (anti-HIV), Remdesivir (anti-Ebola), Favipiravir, and Dipyridamole (anti-hypertensive) [2][3][4][5][6][7][8][9][10][11][12][13]. Also, an anti-acid (Famotidine) is also being promoted [14].…”
Section: Introductionmentioning
confidence: 99%
“…Several drugs have recently been either suggested or being clinically administered to relive the symptoms of covid-19. These include dapagliflozin (sodium glucose cotransporter 2; SGLT2 inhibitor; an antidiabetic), Lopinavir/ Ritonavir, Darunavir/Umifenovir (anti-HIV), Remdesivir (anti-Ebola), Favipiravir, and Dipyridamole (anti-hypertensive) [2][3][4][5][6][7][8][9][10][11][12][13]. Also, an anti-acid (Famotidine) is also being promoted [14].…”
Section: Introductionmentioning
confidence: 99%
“…However, lower dosage showed enough safety and efficacy to treat these patients [169] , [170] , [171] , [172] . HCQ has been shown to be less toxic compared to CQ, and thus it is a reasonable treatment option [173] . However, several studies showed the controversial usage of HCQ for COVID-19 .…”
Section: Discussionmentioning
confidence: 99%
“…chloroquine (A ralan ® ), a well-known anti-malarial and anti-autoimmune agent, has long been used to treat malaria (85) and autoimmune diseases such as systemic lupus erythematosus and rheumatoid arthritis (86), Hydroxychloroquine (Plaquenil ® ) is synthesised by introducing a hydroxyl group into chloroquine. Animal studies have demonstrated that Plaquenil ® is much less toxic than chloroquine (10,(87)(88)(89).…”
Section: Current Therapeutic Modalities For Covid-19mentioning
confidence: 99%